Legal Responsibility of Third Parties for Patent Infringenment - Hasudungan, Andrie Cornelius; Dirkareshza, Rianda (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
Patent rights not only facilitate new inventions but also encourage research and development through clear legal protection. They protect inventors from the unauthorized use or exploitation of their work. Patent infringement is a significant issue in intellectual property law that involves third parties. These third parties can be held legally accountable if they are involved in supplying or distributing products that infringe on patent rights. The aim of this research is to assess the effectiveness of patent law in protecting patent holders and to understand the responsibilities of third parties regarding patent infringement in Indonesia. The methodology used in this study is normative legal research with a statute approach. The statute approach is a research method that prioritizes legal materials in the form of legislation as the primary reference in conducting research. The findings indicate that although patent law in Indonesia provides a clear foundation for protecting the rights of patent holders, its implementation still faces challenges that reduce its effectiveness. One of the indicators of the lack of effectiveness of a regulation is that, despite some years with zero cases/complaints, the number of cases reappears in subsequent years, indicating that the system fails to maintain its effectiveness. Weak law enforcement creates uncertainty for patent holders. While there are mediation and arbitration mechanisms available, inconsistent implementation worsens the situation. Furthermore, third parties involved in patent infringement in Indonesia have legal responsibilities that must be fulfilled. Those who infringe patents can be subject to Article 161 of the Patent Law, which may impose penalties of up to four years in prison and/or fines of up to IDR 1 billion, with lighter sanctions for simple infringements. Keywords: Patent Protection; Responsibility; Third Parties